Tax System Sustainability Evaluation: A Model for EU Countries - Danuše Nerudová; David Hampel; Jitka Janová; Marian Dobranschi; Petr Rozmahel (Intereconomics, 2019)
We follow the multi-dimensional approach to socio-economic sustainability and distinguish among the needs of society in the four dimensions that make up the basic pillars in our model. Thus, we focus on the sustainable development of the economy, society, environment and institutions.
Keywords: 330